A New Simulated Grounded Inductor Based on Two NICs, Two Resistors and a Grounded Capacitor - Yuce, E.; Alpaslan, H.; Minaei, S.; Ayten, U. E. (SPRINGER BIRKHAUSER, 2021)
This paper introduces a simulated grounded inductor (SGI) circuit realization based on two terminal active devices, namely negative impedance converters. The proposed SGI contains a minimum number of passive components when compared to its two terminal active device-based realization counterparts in the literature. It includes a grounded capacitor that is an advantage in integrated circuit process. Nonetheless, a single resistive matching constraint is needed for its realization. SPICE simulations are performed with 0.13 mu m CMOS IBM technology parameters with supply voltages of +/- 0.75 V. Also, an experimental study is included to verify the theory.
Keywords: Simulated grounded inductor; Two terminal active devices; NIC; DO-DVCC; Analog filter; MINIMUM NUMBER; CURRENT CONVEYORS; LOSSLESS; REALIZATION; Engineering